The Influence of Product Quality and Word of Mouth on Wardah Cosmetics Purchase Decisions in Batam City - Elfrida Br Simangunsong; Suhardi Suhardi (Komunitas Dosen Indonesia, 2023)
The aim of this study was to assess the impact of both product quality and creativity on the purchasing choices of Wardah Cosmetics customers in Batam City, both individually and in combination. This research employed a quantitative approach, utilizing a non-probability purposive sampling design or, alternatively, a probability sampling method. Data collection involved distributing questionnaires to 272 participants, and the analysis was conducted using SPSS version 25 software. The findings of the study are supported by the t-test statistic, where the calculated t-value for product quality (X1) was 10.649, exceeding the critical t-table value of 1.968. This indicates that product quality (X1) significantly and positively influences the purchasing decisions of Wardah Cosmetics customers in Batam City on a partial basis. Similarly, for the word of mouth variable (X2), the calculated t-value was 9.559, surpassing the critical t-table value of 1.968, indicating a significant and positive partial influence on the decision to purchase Wardah Cosmetics in Batam City. Furthermore, the study demonstrated a simultaneous and significant positive relationship between the product quality (X1) and word of mouth (X2) variables and the purchasing decision variable (Y), as evidenced by their combined F-value of 791.190, which is greater than the critical F-table value of 3.03. Additionally, the significance level for the product quality (X1) and word of mouth (X2) variables was 0.000, which is less than the significance threshold of 0.05. Consequently, this research supports the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1).